2016
DOI: 10.1186/s12889-016-2937-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of micro health insurance in providing financial risk protection in developing countries- a systematic review

Abstract: BackgroundOut of pocket payments are the predominant method of financing healthcare in many developing countries, which can result in impoverishment and financial catastrophe for those affected. In 2010, WHO estimated that approximately 100 million people are pushed below the poverty line each year by payments for healthcare. Micro health insurance (MHI) has been used in some countries as means of risk pooling and reducing out of pocket health expenditure. A systematic review was conducted to assess the extent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(69 citation statements)
references
References 43 publications
2
58
1
2
Order By: Relevance
“…Being insured was significantly associated with higher odds of utilizing both outpatient and inpatient health services. The finding is consistent with other studies on utilization in other parts of Ghana and Africa [19, 20]. A study in Accra, Ghana’s capital city, showed that registered clients of the NHIS were significantly more likely to receive prescriptions, visit clinics, and use formal health facilities when in need [21].…”
Section: Discussionsupporting
confidence: 90%
“…Being insured was significantly associated with higher odds of utilizing both outpatient and inpatient health services. The finding is consistent with other studies on utilization in other parts of Ghana and Africa [19, 20]. A study in Accra, Ghana’s capital city, showed that registered clients of the NHIS were significantly more likely to receive prescriptions, visit clinics, and use formal health facilities when in need [21].…”
Section: Discussionsupporting
confidence: 90%
“…In line with the findings above, economic outcomes still dominate across all studies, irrespective of quality, followed by gender and social outcomes. ., Hidalgo, 2009Steinert et al, 2018Vaessen et al, 2013Awaworyi, 2014Habib et al, 2016Peters et al, 2016Reshmi et al, 2017Stewart et al, 2012Stewart et al, 2010Arrivillaga et al, 2014Yang et al, 2013Cole et al, 2012Kennedy et al, 2012Pande et al, 2012Madhani et al, 2015Palmkvist et al, 2015Awaworyi et al, 2016Awaworyi, 2015 F I G U R E 3 Number of primary studies per meta-study (11 medium-/high-confidence meta-studies highlighted Total 183 63 24 96 22 72 38 37 14 11 medium-and high-confidence studies Worth examining also is the number of outcomes reported by type of synthesis approach, as outlined in Figure 7, below.…”
Section: Discussionmentioning
confidence: 99%
“…As an example of this approach, mutual health organisations or mutual health insurances have recently become a popular financing solution in some low-income and middle-income countries, especially in Africa 31 32. These mechanisms have not been well explored in Latin America, however, and so further research to investigate their feasibility in Guatemala and other Latin American countries will be important.…”
Section: Global Health Problem Analysismentioning
confidence: 99%